Diagnosis of Urinary Tract Urolithiasis using Computed Tomography: Urinary Tract Urolithiasis using Computed Tomography - Bano, Shehr; John, Akash; Ali, Abid; Qaiser, Hateem; Ashfaq, Nayyar (Pakistan Journal of Health Sciences, 2022)
Renal stone disease is the most common urinary system disease, existing in third after urinary tract infection and prostate disease in urological departments and accounting for 10-15% of all cases. Objective: To evaluate urolithiasis on Computed Tomography (CT KUB). Methods: It is a cross sectional study carried out at the private Sector Hospital of Gujrat, Pakistan over 4 months from December 2021 to March 2022. A sample size of 50 patients was calculated via a convenient sampling approach using the mean from previous related studies. Patients with kidney stones diagnosed on CT KUB scan were included after informed consent. The data was analyzed and entered using SPSS version 21. Results: The result of this study revealed that people in their 51s and 60s are the most affected and that males are 56% more likely than females to have kidney stones. The right kidney is the most prevalent location for stones. The calcium oxalate kidney stone scale ranged from 1 to 50 mm in diameter. And the correlation between the location of kidney stone and size is 0.94 so there is a moderate correlation between stone size and location. Conclusion: In conclusion, the CT equipment is fully capable of detecting and measuring stones, as well as determining their type and major component